COMPARATIVE ADVANTAGES OF COCONUT SUGAR AGROINDUSTRY: CASE STUDY IN PENGALUSAN VILLAGE, MREBET DISTRICT, PURBALINGGA REGENCY, CENTRAL JAVA, INDONESIA - Qomariyah, Siti; Suhartini; Nugroho, Condro Puspo (Agricultural Socio-Economics Journal, 2024)
The objectives of this research were to analyze the financial feasibility and the comparative advantages of the coconut sugar agroindustryin the form of crystal sugar and block sugar. This research is a case study in the centre of coconut sugar industry in Purbalingga Regency, namely Pengalusan Village, Mrebet District which was chosen purposively. Survey method was used in this research by interviewing 40 respondents for coconut crystal sugar agroindustry and 24 respondents of coconut block sugar agroindustry for primary data. This research also used secondary data from Statistical Agency. The analytical method used were the analysis of costs, revenues, profits, and R/C ratio, as well as DRC (Domestic Resource Cost) analysis. The results showed that the R/C ratio analysis for crystal sugar agroindustry was 1.11, and for block sugar agroindustry was 1.04. It means that both agroindustry are financially profitable so that they are feasible to do, though they just receive small profit.  The results of the DRC ratio analysis showed that the coconut crystal sugar agroindustry has a comparative advantage so that it can be produced cost-efficiently when using domestic resources. The coconut crystal sugar agroindustry in Pengalusan Village has a comparative advantage with a DRCR (Domestic Resource Cost Ratio) value of 0.505, which means that agroindustry is efficient in allocating domestic resources and is able to save US$ 0.505 of foreign exchange from every US$ 1 unit. Therefore, to meet the demand for coconut sugar, it is better to increase domestic production.